Structure and Composition of Vegetation and Carbon Stock Calculation in a Natural Lowland Forest of Plantation Forest Landscape - D Priatna; NM Heriyanto; I Samsoedin; Supriatno Supriatno; U Wiharjo; E Laksana (Universitas Nasional Jakarta, 2022)
In Indonesia, every concession of industrial plantation forest must leave at least 10% from the size of the concession as natural forest and set aside for protected area. We examined the forest structure and composition through a one-hectare permanent sampling plot (PSP) within three forest cover classes, open land, scrub and young regeneration forest. Surveys showed that there were 143 trees (>10 cm dbh) of 23 species in the Open Land PSP (dominated by Euphorbiaceae, Myristicaceae and Rutace families), 407 trees from 48 species in the Scrub PSP (Euphorbiaceae, Lauraceae and Sapindaceae), and 486 trees from 67 species in the Young Regeneration Forest PSP (Euphorbiaceae, Lauraceae and Annonaceae). Biomass and carbon stock determined through the trees ≥ 10 cm dbh in each forest cover classes. With a Chave formula found that in Open Land stored 15.6 ton C/Ha, in Scrub stored 63.4 ton C/Ha, and in Young Regeneration Forest stored 83.8 ton C/Ha. Calculated that there is around 4.7 million ton C stored in those various forest and vegetation covers within conservation area inside plantation forest concessions at landscape scale. This can be contributed to the efforts of emission reduction at the sub-national level.